Urgensi Reformulasi Ketentuan Pembelian Terselubung Dalam Undang-Undang Narkotika Untuk Mencegah Penyalahgunaan Wewenang Oleh Penegak Hukum (RechtJiva, 2024)
This research aims to study the confusing norm concerning the application of enquiry into the case of undercover buy as in Article 79 of Law Number 35 of 2009 concerning Narcotics, which is not further elaborated in terms of the implementation of the law concerned, which leads further to another issue of field implementation and legal loophole to enforce the law in terms of permit to own narcotics for private use. This research employs normative-juridical methods and statutory, conceptual, and comparative approaches. The research results reveal that there is an urgency to reformulate the provision of undercover buy in Law Number 35 of 2009 concerning Narcotics because the Criminal Code Procedure does not specifically regulate the technique of undercover buy. This research, therefore, compares the undercover buy between Indonesia and the United States of America and Britain.